Principles of Mathematical Economics II: Solutions Manual, Supplementary Materials and Supplementary Exercises - Vali, Shapoor (Springer, 2015)
This manual provides solutions to approximately 500 problems appeared in various chapters of the text Principles of Mathematical Economics. In some cases, a detailed solution with the additional discussion is provided. At the end of each chapter, new sets of exercises are given.